Obesity inequality and the changing shape of the bodyweight distribution in China - Peng Nie; Lanlin Ding; Alfonso Sousa-Poza (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
Using data from the China Health and Nutrition Survey (CHNS), this study analyses changes in bodyweight (BMI and waist circumference) distributions between 1991 and 2011 among adults aged 20+ in China. To do so, we quantify the source and extent of temporal changes in bodyweight and then decompose the increase in obesity prevalence into two components: a rightward shift of the bodyweight distribution (mean growth) and a (re)distributional skewing. Our analysis reveals a clear rightward distributional shift combined with a leftward skewing. Although the relatively large size of this skewing in the first decade analysed reflects an increase in obesity inequality, this inequality growth subsides in the second decade. Nevertheless, over the entire 20-year period, obesity inequality increases significantly, especially among females, younger age groups, rural residents and individuals with low socioeconomic status.
urn:nbn:de:bsz:100-opus-15403
Keywords: D30; D63; I10; I14; 330; BMI; Waist circumference; Obesity inequality; Decomposition; China